Identifikasi Ayat-Ayat Al Qur’an Berhubungan dengan Motivasi Belajar dalam Ilmu Sains - Intan Fathia Rahmi Rahmi; Yollanda Syafmitha; Sherli Fransiska; Ardi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2023)
Education and teaching is a goal-conscious process. In the field of education, there is no doubt that the existence of the Al-Qur'an has influenced the education system of the Prophet and his companions. The Al- Quran can also provide inspiration and motivation in various aspects of life, including in the context of science learning. The purpose of writing this article is to identify some Al- Quran verses related to learning motivation to study science for students. The method used in this research is the literature review method by reviewing several articles related to the topics discussed in this study. The results of this study show that learning motivation is very important to be given to everyone, especially for students who are studying at school level. By understanding the Al- Quran messages about learning motivation in the context of science, students can explore spiritual wisdom and apply it in their journey to learn and understand the universe.